Enhanced higher temperature irreversibility field and critical current density in MgB2 wires with Dy2O3 additions. (12th January 2021) - Yang, Y; Sumption, M D; Rindfleisch, M; Tomsic, M; Collings, E W
Abstract: Bulk samples of magnesium diboride (MgB2 ) doped with 0.5 wt% of the rare earth oxides (REOs) Nd2 O3 and Dy2 O3 (named B-ND and B-DY) prepared by standard powder processing, and wires of MgB2 doped with 0.5 wt% Dy2 O3 (named W-DY) prepared by a commercial powder-in-tube processing were studied. Investigations included x-ray diffractometry, scanning- and transmission electron microscopy, magnetic measurement of superconducting transition temperature ( T c ), magnetic and resistive measurements of upper critical field ( B c2 ) and irreversibility field ( B irr ), as well as magnetic and transport measurements of critical current densities versus applied field ( J cm ( B ) and J c ( B ), respectively). It was found that although the products of REO doping did not substitute into the MgB2 lattice, REO-based inclusions resided within grains and at grain boundaries. Curves of bulk pinning force density ( F p ) versus reduced field ( b = B / B irr ) showed that flux pinning was by predominantly by grain boundaries, not point defects. At all temperatures the F p ( b ) of W-DY experienced enhancement by inclusion-induced grain boundary refinement but at higher temperatures F p ( b ) was still further increased by a Dy2 O3 additive-induced increase in B irr of about 1 T at all temperatures up to 20 K (and beyond). It is noted that Dy2 O3 increases B irr and that it does so, not just at 4 K, but in the higher temperature regime. This important property, shared by a number of REOs and other oxides promises to extend the applications range of MgB2 conductors.